Manajeman Pendidikan Karakter dalam Membina Akhlak Siswa: Studi Kasus di MA Al Zaytun Indramayu - Lutfi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study examines character education management at MA Al-Zaytun Indramayu, recognized as a pioneer of character education in Indonesia since 1999. Using a qualitative descriptive approach, this research explores four management aspects: planning, organizing, implementation, and supervision. The findings reveal that character education planning at MA Al-Zaytun was formulated by a dedicated team led by AS Panji Gumilang and realized through a modern boarding school system with a “one pipe system” approach. Organizing involves the Indonesian Pesantren Foundation (YPI), the Board of Teachers, and all teaching staff, utilizing modern education management principles. Implementation is conducted comprehensively through formal, non-formal, and informal channels, such as the study of Statecraft and Human Rights (KHAM) and extracurricular activities. Supervision is systematically carried out through observation, direct inspections, and regular discussions, led by AS Panji Gumilang. This study highlights the critical role of management in the successful implementation of character education based on values of peace and tolerance.